Primary pericardial synovial sarcoma presenting as cardiac tamponade (Indian Journal of Case Reports, 2026)
Primary malignant cardiac neoplasms are a rare entity. Malignant pericardial tumors may present with pericardial effusion or non-specific symptoms. We report about a middle-aged male patient who presented with cardiac tamponade and was diagnosed with biphasic phenotype of primary pericardial synovial sarcoma, using histopathology and immunohistochemistry. Diagnosis of pericardial synovial sarcoma requires a multipronged approach involving clinical, imaging, histopathological and cytogenetic evaluation. Demonstration of a specific cytogenetic alteration (chromosomal translocation t(X;18)(p11.2;q11.2) SYT-SSX) remains the ideal confirmatory test. However, in resource constrained settings, a detailed histopathological examination combined with immunohistochemistry, specifically nuclear staining for Transducin like enhancer of slit-1 in tumor cells is useful for accurate diagnosis, due to its high sensitivity and specificity. Early diagnosis followed by prompt initiation of therapy may lead to improved outcomes despite the dismal prognosis associated with this neoplasm